Promoting Dinuclear‐Type Catalysis in Cu1–C3N4 Single‐Atom Catalysts. Issue 33 (15th July 2022) - Song, Jingting; Chen, Zhongxin; Cai, Xiangbin; Zhou, Xin; Zhan, Gaolei; Li, Runlai; Wei, Pingping; Yan, Ning; Xi, Shibo; Loh, Kian Ping
Abstract: Reducing particle size in supported metal catalysts to single‐atom level isolates the active metal sites and maximizes the atomic utilization efficiency. However, the large inter‐atom distance, particularly in low‐loading single‐atom catalyst (SAC), is not favorable for a complex reaction where two (or more) reactants have to be activated. A key question is how to control the inter‐atom distances to promote dinuclear‐type coactivation at the adjacent metal sites. Here, it is reported that reducing the average inter‐atom distance of copper SACs supported on carbon nitride (C3 N4 ) to 0.74 ± 0.13 nm allows these catalysts to exhibit a dinuclear‐type catalytic mechanism in the nitrile–azide cycloaddition. Operando X‐ray absorption fine structure study reveals a dynamic ligand exchange process between nitrile and azide, followed by their coactivation on dinuclear Cu SAC sites to form the tetrazole product. This work highlights that reducing the nearest‐neighbor distance of SAC allows the mechanistic pathway to diversify from single‐site to multisite catalysis. Abstract : A dinuclear‐type nitrile–azide cycloaddition in a 21 wt% carbon‐nitride‐supported copper single‐atom catalyst (Cu1 –C3 N4 ) is demonstrated by reducing the inter‐atom distance within the diffusion length of reactants, thus transforming the catalytic pathway from a poorly active single‐site to dinuclear‐type mechanism.